Scale dependence of species–area relationships is widespread but generally weak in Palaearctic grasslands. (16th June 2021) - Zhang, Jinghui; Gillet, François; Bartha, Sándor; Alatalo, Juha Mikael; Biurrun, Idoia; Dembicz, Iwona; Grytnes, John‐Arvid; Jaunatre, Renaud; Pielech, Remigiusz; Van Meerbeek, Koenraad; Vynokurov, Denys; Widmer, Stefan; et al.
Abstract: Questions: Species–area relationships (SARs) are fundamental for understanding biodiversity patterns and are generally well described by a power law with a constant exponent z . However, z ‐values sometimes vary across spatial scales. We asked whether there is a general scale dependence of z ‐values at fine spatial grains and which potential drivers influence it. Location: Palaearctic biogeographic realm. Methods: We used 6, 696 nested‐plot series of vascular plants, bryophytes and lichens from the GrassPlot database with two or more grain sizes, ranging from 0.0001 m² to 1, 024 m² and covering diverse open habitats. The plots were recorded with two widespread sampling approaches (rooted presence = species "rooting" inside the plot; shoot presence = species with aerial parts inside). Using Generalized Additive Models, we tested for scale dependence of z ‐values by evaluating if the z ‐values differ with gran size and tested for differences between the sampling approaches. The response shapes of z‐ values to grain were classified by fitting Generalized Linear Models with logit link to each series. We tested whether the grain size where the maximum z‐ value occurred is driven by taxonomic group, biogeographic or ecological variables. Results: For rooted presence, we found a strong monotonous increase of z ‐values with grain sizes for all grain sizes below 1 m². For shoot presence, the scale dependence was much weaker, with hump‐shaped curves prevailing. Among the environmental variables studied, latitude, vegetation type, naturalness and land use had strong effects, with z ‐values of secondary peaking at smaller grain sizes. Conclusions: The overall weak scale dependence of z ‐values underlines that the power function generally is appropriate to describe SARs within the studied grain sizes in continuous open vegetation, if recorded with the shoot presence method. When clear peaks of z ‐values occur, this can be seen as an expression of granularity of species composition, partly driven by abiotic environment. Abstract : Fine‐grain species‐area relationships can be well described with the power function, but at closer look the exponent z (a measure of multiplicative beta diversity) might vary across scales. Using nearly 7, 000 nested‐plot series from Palaearctic open habitats, we found that for rooted presence sampling z strongly increases from 1 m² towards smallest grains, whereas for shoot presence sampling there is typically a weak peak somewhere below 1 m². Peak position was mainly influenced by taxonomic group, latitude and naturalness.